2018
DOI: 10.1053/j.gastro.2018.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Regulation of the Uridine Phosphorylase 1 Gene and Uridine-Induced DNA Damage in Colon in African Americans and European Americans

Abstract: We found vitamin D to increase expression of UPP1, leading to reduce uridine-induced DNA damage, in colon cells and organoids. A polymorphism in UPP1 found more frequently in African Americans than European Americans reduced UPP1 expression upon cell exposure to 1α,25(OH)D. Differences in expression of UPP1 in response to vitamin D could contribute to the increased risk of CRC in African Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Note that previous studies involving colon organoids are often associated with much smaller sample sizes, typically ten or less [13,[17][18][19][20]. We performed differential expression analysis on pseudo-cohorts of multiples of five pairs generated by random sampling.…”
Section: Carcinogen Treatment Of Colon Organoids Leads To Consistent Patterns Of Differential Expressionmentioning
confidence: 99%
“…Note that previous studies involving colon organoids are often associated with much smaller sample sizes, typically ten or less [13,[17][18][19][20]. We performed differential expression analysis on pseudo-cohorts of multiples of five pairs generated by random sampling.…”
Section: Carcinogen Treatment Of Colon Organoids Leads To Consistent Patterns Of Differential Expressionmentioning
confidence: 99%
“…UPP1, which is involved in pyrimidine metabolism, regulates uridine homeostasis and promotes pyrimidine salvage 47 . Previous studies have reported that UPP1 is involved in the pathogenesis of colon cancer 48 , glioma 26 , breast cancer 49 , thyroid cancer 50 , oral squamous cell carcinoma 51 , pancreatic cancer 52 , and lung adenocarcinoma 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, 1,25(OH) 2 D 3 inhibited the protumoral activation of patient-derived colon normal fibroblasts (NFs) and cancer-associated fibroblasts (CAFs) and a 1,25(OH) 2 D 3 -associated gene signature imposed in CAFs correlated with a better prognosis in CRC ( Ferrer-Mayorga et al, 2017 ). Nevertheless, there is still a lack of sufficient and potent evidence from prospective clinical trials at present, and nonresponse to vitamin D may result from molecular mutation and regulation of the cancer-associated pathway ( Barry et al, 2017 ; Bhasin et al, 2018 ). Thus, it is essential to further reveal the biological mechanisms illustrating the antitumor role of vitamin D 3 in CRC.…”
Section: Introductionmentioning
confidence: 99%